Penelusuran Kompetensi Profesional Guru Bahasa Inggris Alumni IAIN Bengkulu dalam Kiprah di Dunia Pendidikan - Zasrianita, Fera; Hariyanto, Endang (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The purpose of this study is to explore the professional competence of English teachers who are alumni of IAIN Bengkulu in their role in the world of work. The research approach used in this study is a qualitative approach with a descriptive analytical research design. The Industrial Revolution 4.0 era has caused major changes in the world of education both at the tertiary and elementary school levels. This study selected high school and junior high school level objects in Kaur, Seluma and South Bengkulu regencies in Bengkulu province. Based on the results of the research and discussion, it is known that English teachers who are alumni of IAIN Bengkulu are mostly spread across three regencies, namely Seluma, South Bengkulu and Kaur Regency, Bengkulu province. Alumni teachers also mostly teach in junior high and high school levels.